Preservation of microvascular barrier function requires CD31 receptor-induced metabolic reprogramming - Kenneth C. P. Cheung (Nature Portfolio, 2020)
The mechanisms that restore endothelial barrier integrity following inflammation-induced breaching are incompletely understood. Here the authors show that the CD31 immune receptor contributes to reestablishing vascular integrity via its effects on endothelial cell metabolism.